(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This paper aims to examine the procedures used in the translation of literary devices into English in Malay literary works which are often influenced by the language and culture of an author. Based on the analysis, the following literary devices are identified, namely allusion, dialect, simile, alliteration, and wordplay. The findings show that translators employ procedures such as literal translation, generalisation, borrowing, adaptation, omission and description to translate the literary devices identified. It is hoped that the problems highlighted in this article can help heighten the translator’s awareness of one of the challenges involved in the translation of Malay literary works and subsequently encourage the translator to explore various approaches which can help minimise loss of meaning in the process of translation. Keywords: literary device, Malay literature, translation procedures, language, culture